2020
DOI: 10.1002/chem.202002678
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of N2 via Formal 1,3‐Haloboration of a Tungsten(0) σ‐Dinitrogen Complex

Abstract: Boron tribromide and aryldihaloboranesw ere found to undergo 1,3-haloboration across one WÀNN moiety of ag roup 6e nd-on dinitrogen complex (i.e. trans-[W(N 2) 2 (dppe) 2 ]). The N-borylated products consist of ar educed diazenido unit sandwiched between aW II center and at rivalent boron substituent (WÀN=NÀBXAr), and have all been fully characterized by NMR andI Rs pectroscopy,e lementala nalysis, and single-crystal X-ray diffraction. Both the terminal Na tom and boronc enteri nt he WÀN=NÀBXAr unit can be fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 83 publications
2
21
0
4
Order By: Relevance
“…Taken together, our results show that all four ligands form stabilizing interactions with the nickelatranes due to a combination of electrostatic, bonding, and dispersion interactions. These are increased if the heavier group 13 atoms are positioned in the bridgehead position, a strategy that becomes particularly relevant for the activation and functionalization of less reactive species, such as N 2 , which agrees with earlier experimental studies …”
Section: Resultssupporting
confidence: 88%
“…Taken together, our results show that all four ligands form stabilizing interactions with the nickelatranes due to a combination of electrostatic, bonding, and dispersion interactions. These are increased if the heavier group 13 atoms are positioned in the bridgehead position, a strategy that becomes particularly relevant for the activation and functionalization of less reactive species, such as N 2 , which agrees with earlier experimental studies …”
Section: Resultssupporting
confidence: 88%
“…The group of Braunschweig has recently shown that the W complex 21 is also reactive towards tri-and dihalo(aryl)boranes. 22 The latter reacted with 21 through a formal 1,3-haloboration, allowing the preparation of boryldiazenido compounds 33 and Ar 34-X (Scheme 9). Chloroboranes reacted more sluggishly than the bromo derivatives.…”
Section: 3 Haloborationmentioning
confidence: 99%
“…Complex 3 was isolated as a greenish solid in a very good 80 % yield and characterized by multinuclear NMR spectroscopy. No signal was observed in the 11 B{ 1 H} spectrum, as often encountered for tricoordinated B centers, especially when they are bonded to a quadrupolar center such as N [37] . X‐ray diffraction analysis of crystals obtained by diffusion of pentane into a THF solution of the complex provided definitive proof of the proposed structure (Supporting Information) [43] .…”
Section: Methodsmentioning
confidence: 97%
“…Simonneau further explored this reactivity using strongly electrophilic derivative (C 6 F 5 ) 2 BH [35, 36] . In 2020, Braunschweig reported the 1,3 addition of a B−Br bond across a W‐NN moiety [37] . Using early transition metals, Fryzuk achieved the 1,2 B‐H addition on N 2 at a bimetallic Ta complex, [38] while Chirik observed the formation of a N−B bond and bridging hydride starting from a side on MN 2 M (M=Zr, Hf) complex [39] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation